Teachers’ knowledge of Asthma in primary schools - "Movahedi M; Moin M; Tavakol M " (Acta Medica Iranica, 2000)
A survey was carried out in 1998-99 among 20 selected primary schools in the north, south, east and west regions of Tehran to determine the level of teachers’ knowledge of asthma. 387 (96.7%) of 400 questionnaires were completed and evaluated. Five items were investigated: “general knowledge”, “symptoms and triggers”, exercise”, treatment” and “individual experience”. Statistical analysis was performed by using counting statistics. For the correlation of items, Spearman correlation coefficients and willcoxon’s test were used. The teachers in primary schools showed a good basic knowledge of asthma and trigger factors of asthma; 40.6% teachers knew that asthma could not be transmitted by virus. There was no statistically significant effect of teaching experience in terms of years, level of education and contact with asthmatic child on the knowledge score. 24% of teachers felt they had the average information about asthma. We suggest that teachers at primary school receive further instructions in this regard.